PENGARUH AUDITOR SWITCHING, REPUTASI KAP DAN FINANCIAL DISTRESS TERHADAP OPINI AUDIT GOING CONCERN - Elza Devi Laksmiati; Suci Atiningsih (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2018)
This study aims to exaamine the effect of auditor switching, reputation of KAP and financial distress towards going concern audit opinion. The sample of this research is obtainable by using the purposive sampling method by focusing on manufactures companies that has been listed on the Indonesia Stock Exchange period 2012-2016. The method used in the research is non probability sampling with purposive sampling technique. Samples were obtained as many as 55 companies by number of observations is 275 samples. The analysis finds result is that the variable auditor switching and financial distress has a significant positive impact on the going concern audit opinion, and reputation of KAP has a significant negative impact on the going concern audit opinion.